Hubungan Pencahayaan Rumah Dengan Kejadian Tuberkulosis Paru Di Wilayah Kerja Puskesmas Tonjong Kabupaten Brebes Tahun 2021 - Ahmad Zakiudin; Nurhastati Rakhmatillah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Tuberculosis is an infectious disease caused by the bacteria mycobacterium tuberculosis which spreads through the air and is transmitted through droplets when a person coughs, sneezes, talks, and spits anywhere. Tuberculosis is still a disease with a high level of morbidity, accompanied by very easy transmission, namely through the air. Therefore, this tuberculosis disease must be handled immediately and carefully if cases are found in an area. The purpose of this study was to determine the relationship between house lighting and the incidence of pulmonary tuberculosis in the working area of ​​Tonjong Health Center, Brebes Regency. This research method is analytical research. The method used in this research is a survey method which is carried out by distributing questionnaires and direct interviews to respondents with a cross sectional study approach. The data obtained were analyzed statistically using the Chi-Square test. From the statistical test results, it was found that the p-value = 0.002, this means that it is smaller than the value of α = 0.05. So it can be concluded that H0 is rejected, meaning that there is a significant relationship between home lighting and the incidence of pulmonary tuberculosis in the work area of ​​the Tonjong Community Health Center, Brebes Regency in 2021. In connection with the results of this study, it is hoped that the community will be able to improve the condition of the house according to the criteria for a healthy house. Such as the addition of ventilation holes, glass tiles. This is because the addition of ventilation can affect sufficient lighting intensity and reduce high humidity levels